2023
DOI: 10.1021/jacs.3c01684
|View full text |Cite
|
Sign up to set email alerts
|

Myth behind Metastable and Stable n-Hexylammonium Bromide-Based Low-Dimensional Perovskites

Abstract: In perovskite solar cells, passivating the surface or interface that contains a high concentration of defects, specifically deep-level defects, is one of the most important topics to substantially enhance the power conversion efficiency and stability of the devices. Long-chain alkylammonium bromides have been widely and commonly adapted for passivation treatment. However, the mechanism behind is still not well explored as the formation route and the exact structure of these alkylammonium bromide-based lowdimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It is well known that the photovoltage of a solar cell is directly related to its internal luminescence ability. 58 Here, we qualitatively demonstrate the reduction in trap density by recording the difference in luminescence performances of the two devices using a photophysical characterization method. 59 As shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…It is well known that the photovoltage of a solar cell is directly related to its internal luminescence ability. 58 Here, we qualitatively demonstrate the reduction in trap density by recording the difference in luminescence performances of the two devices using a photophysical characterization method. 59 As shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…53 Subsequently, more and more studies have been reported on the long-chain organic spacer cations represented by BA ( e.g. n -hexylammonium (HA), 54 ethylammonium (EA), 55 propylammonium (PA), 56 octylammonium iodide (OA), 57 which greatly promoted the development of 2D PR PSCs.…”
Section: D Rp Perovskite Materials Based On Different Spacer Cationsmentioning
confidence: 99%
“…Compared to their pure iodide counterparts, Br/Cl-incorporated 2D perovskites are thermodynamically more stable due to a lower formation energy from the relaxed lattice strain . For instance, the post-treatment of HABr and OABr gave rise to mixed-halide quasi-2D perovskite capping layers of HA 2 FAPb 2 Br 2 I 5 ( n = 2) and OA 2 FAPb 2 Br 2 I 5 ( n = 2), respectively. , Notably, the exposure of the 3D perovskite layer to the corrosive IPA with a high solubility of FAI tends to create a PbI 2 -rich surface that facilitates the formation of 2D perovskite of HA 2 PbI 2 Br 2 ( n = 1) by the chemical reaction between PbI 2 and HABr at the surface, while the use of nonreactive CF results in quasi-2D perovskite of HA 2 FA n ‑1 Pb n I 3 n ‑1 Br 2 ( n ≥ 2) upon the gradual intercalation of HABr into the crystal lattices of FAPbI 3 . , Moreover, oxidative Cl 2 generated in the fresh CF solvent after light soaking could offer a viable Cl source for the successful preparation of Cl-doped bilayer 2D-3D PHSs, where the identified Cl 2 /I- redox reaction triggers the Ostwald ripening for the secondary growth of 3D perovskite grains (∼5 μm) . The easy Cl 2 permeation enables effective overall defect passivation within the 3D perovskite layers as well as the buried interface, thus leading to a high PCE of 24.21% in the Cl-incorporated target devices.…”
Section: Evolution Roadmap Of Bilayer 2d-3d Phssmentioning
confidence: 99%